(2/3)4x+13=3x-8

Simple and best practice solution for (2/3)4x+13=3x-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2/3)4x+13=3x-8 equation:



(2/3)4x+13=3x-8
We move all terms to the left:
(2/3)4x+13-(3x-8)=0
Domain of the equation: 3)4x!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+2/3)4x-(3x-8)+13=0
We multiply parentheses
8x^2-(3x-8)+13=0
We get rid of parentheses
8x^2-3x+8+13=0
We add all the numbers together, and all the variables
8x^2-3x+21=0
a = 8; b = -3; c = +21;
Δ = b2-4ac
Δ = -32-4·8·21
Δ = -663
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 25=5c-15 | | 6(x-1)=2×+10 | | 2/3(y-6)=-(y-2)+1 | | 5x-7x=19-6 | | 8-8c=-8c-3c-10 | | -9u-36=9(u+2) | | 20+4.25w=75.25 | | 2+15*z=92 | | 6=3(u−5) | | 135-2g=3g | | -4-6n=14 | | a/12+2=9 | | 7n-3.2n+6.2=17.9 | | 6(x+2)=4x-(12-2x) | | 10(x-3)+15x=20 | | 24=-8v+5(v+6) | | 11=-9i | | n−n=0 | | r/5-15=2 | | -12(-10+x)=288 | | 13=m/12-5 | | -4b+4=7-3b | | 7x+;3=52 | | –3s+10=–s−10 | | 2.5x-4=3.4x+2 | | (9x+10)=(7x+24) | | 13a+9=61 | | 5x+9=292X+5=7 | | 6+9g=6g | | 27=j+14 | | 10-3p=-p-8 | | 12=-2+2y |

Equations solver categories